2021
DOI: 10.3889/oamjms.2021.5649
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Knowledge of First Aid Treatment Related to Burn Injury in the Rural Region of Kulon Progo, Indonesia

Abstract: BACKGROUND: We investigated the epidemiology and the knowledge of first aid regarding to burns in the rural area of Kulon Progo, located in Indonesia. Although 44% of Indonesia’s population resides in rural areas, data of burn in Indonesia are very limited to national referral centers located in Indonesia’s largest cities. We also surveyed the patients and families of these burn patients to try to understand their knowledge on the first aid of burns. AIM: We wanted to explore and discover what myths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…In our study, caregivers' knowledge of burning first aid in those attending burn units was found to be poor in 202(66.2%) of study participants. This finding is consistent with findings from Indonesia 66% [ 17 ]. The likely reason for the consistency might be the similarity of the study area; both were conducted at burn units among caregivers.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, caregivers' knowledge of burning first aid in those attending burn units was found to be poor in 202(66.2%) of study participants. This finding is consistent with findings from Indonesia 66% [ 17 ]. The likely reason for the consistency might be the similarity of the study area; both were conducted at burn units among caregivers.…”
Section: Discussionsupporting
confidence: 94%
“…The likely reason for the consistency might be the similarity of the study area; both were conducted at burn units among caregivers. The result is also higher than a similar study conducted in Palestine, Pakistan, and Ghana, 43%, 44%, and 24%, respectively [ 13 , 16 , 17 ]. The discrepancy may be attributed to the difference in the study population sample size and level of education.…”
Section: Discussioncontrasting
confidence: 70%
“…This may be related to the occupation of the samples in this study which was mostly as professional work group, where burn injuries were more common in the workplace. However, research conducted by Ramli et al 7 showed the reversed result where the age group under 18 years old was the most affected by burns, namely as much as 48%. Several other studies even assessed that the age group of children under 5 years was more susceptible to being affected because of ignorance of things that were at risk of burns.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, several factors can influence changes in the wound or the occurrence of pressure, namely the patient's nutritional status, age, weight, and the strict concept of changing position. In addition, it is also essential to socialize and increase knowledge and public awareness about healthy lifestyles (7,25).…”
Section: Discussionmentioning
confidence: 99%